Moonlighting in myxobacteria: measuring the covariation in GAPDH. Issue Volume 1(2019)Issue A (8th March 2019) - Zwarycz, Allison; Whitworth, David
Abstract : Myxobacteria are an order of well-known social predators that able to prey upon a wide range of microbes (including fungi and bacteria). It is currently unknown how they are able to consume such a wide range of prey, although moonlighting proteins, those possessing more than one function, appear to be involved. One moonlighter, is the virtually ubiquitous enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH). Typically present in the cytoplasm, it has also been found on the outer surface of cells, in the extracellular matrix, and secreted through membrane vesicles. In various pathogenic organisms, GAPDH has been shown to have adhesive properties, binding to several types of human connective tissues. Myxobacterial predation can be viewed as analogous to pathogenic infection, and there is evidence that GAPDH might be involved in attacking prey cells. To complement experimental analyses of the predatory role of GAPDH in myxobacteria, we undertook sequence analysis including multiple sequence alignment (MSA) and covariation analyses. Covariation calculations, using a variety of metrics and matrices, have been used to identify areas and individual residues where structural, functional or phylogenetic correlations occur within the sequence. The MSA data highlighted key conserved residues, likely involved in the catalytic reaction and potentially involved in adhesion. The covariation scores suggest compensatory mutations have taken place in discrete locations along the sequence. These results can be used to selectively mutate residues in order to determine their effect in predation.